South Korea's new nationalism : the end of "one Korea"? - Campbell, Emma, 1976- (FirstForumPress, a division of Lynne Rienner Publishers, Inc., 2016)
Why have traditional views of national identity in South Korea-views that for years drove a demand for reunification-been challenged so dramatically in recent years? What explains the growing ambivalence and even antagonism of South Korean young people toward unification with North Korea? Emma Campbell addresses these related puzzles, exploring the emergence of a new kind of nationalism in South Korea and considering what this development means for the country's future.